PENERAPAN ANALISIS KONTEN PADA POLA PENGEMBANGAN PARIWISATA HALAL BERBASIS MASYARAKAT DI GEOSITE LEMBAH SEMBALUN - Idham Kholid; Akhmad Saufi; Baiq Handayani Rinuastuti (Master of Management, Mataram University, 2020)
This study aims to find the results of content analysis in determining the pattern of developing halal tourism based community in Geosite Lembah Sembalun. Data collection was colledted through observation, in-depth interviews and documentation. The results of this study obtained 3 categories and 11 themes through open and axial coding processes. In this study, it is stated that the pattern of developing halal tourism based community in Geosite Lembah Sembalun is spontaneous and induced participation obtained from 3 categories of content analysis, namely community participation in involvement phase, degree of participation and community participation in developing halal tourism.Keywords: Content Analysis, Halal Tourism, Pattern, Participation, Geosite Lembah Sembalun